Competitive Growth of Ge Quantum Dots on a Si Micropillar with Pits for a Precisely Site-Controlled QDs/Microdisk System - Jia Yan; Zhifang Zhang; Ningning Zhang; Qiang Huang; Yan Zhan; Zuimin Jiang; Zhenyang Zhong (Nanomaterials, 2023)
Semiconductor quantum dots (QDs)/microdisks promise a unique system for comprehensive studies on cavity quantum electrodynamics and great potential for on-chip integrated light sources. Here, we report on a strategy for precisely site-controlled Ge QDs in SiGe microdisks via self-assembly growth of QDs on a micropillar with deterministic pits and subsequent etching. The competitive growth of QDs in pits and at the periphery of the micropillar is disclosed. By adjusting the growth temperature and Ge deposition, as well as the pit profiles, QDs can exclusively grow in pits that are exactly located at the field antinodes of the corresponding cavity mode of the microdisk. The inherent mechanism of the mandatory addressability of QDs is revealed in terms of growth kinetics based on the non-uniform surface chemical potential around the top of the micropillar with pits. Our results demonstrate a promising approach to scalable and deterministic QDs/microdisks with strong light–matter interaction desired for fundamental research and technological applications.